Cultural diversity on programs of Psychology - Maldonado Santiago, Norma (2011)
The Cultural Diversity courses on Programn of Psychology should raise students’ awareness towards Others who tend to provoke negative emotions because of being different. The university courses and professional practices seem to respond to a particular culture while pretending to be universal in their postures. A qualitative study was conducted in which syllabuses of cultural diversity courses corresponding to different academic institutions from Puerto Rico, Europe and Latin America were examined. The content analysis revealed that the approach to the subject typically corresponds to the country’s idiosyncrasy, psychosocial circumstances and particular regulations as well as the intervention of organizations and accrediting  agencies. It is discussed the inherent diversity to the psychology, even in their teaching as in its application.